EFFECTIVE METHODS OF TEACHING ENGLISH TO YOUNG LEARNERS (Eureka Journal of Education & Learning Technologies, 2026)
This article explores effective strategies for teaching English to young children, highlighting the significance of interactive and child-focused methods. The research is grounded in a qualitative review of literature by leading experts in the area, including Harmer, Scott and Ytreberg, Ur, Brewster, and Krashen. The results indicate that approaches like game-based learning, songs, storytelling, and Total Physical Response boost children's motivation, engagement, and language advancement. The importance of the teacher's role in fostering a nurturing and dynamic classroom environment is underscored, along with the necessity of engaging and age-appropriate activities. The article concludes that utilizing these research-backed strategies not only enhances language skills but also promotes a favorable attitude towards learning English, establishing a robust foundation for ongoing language development.
Keywords: young learners, motivation, English language teaching, child – centered methods, storytelling, game – based learning.